THE IMPORTANCE OF STRATEGIC COMPETENCE IN SUPPORTING STUDENTS’ SPEAKING PERFORMANCE - Dwi Warry Octaviana (Journey: Journal of English Language and Pedagogy, 2021)
Sometimes, people may request to offer our viewpoints on a specific subject. It is once in a while difficult to verbally communicate our opinion to others. Those may have trouble putting our thoughts into words or may even dread be addressing to others. So, communication is not effectively delivered. Therefore, we should be able to find an effective way to continue expressing idea using suitable words. Due to this problem, this study was aimed to investigate whether strategic competence has positive relationship with speaking performance and to discover the varieties of strategic competence undertaken by the students particularly. A descriptive method used in this study. The data needed were obtained through a sample consisting of 14 students at Senior High School in Garut. The data analysis shows that there is positive relationship between strategic competence and speaking performance. In addition, the communication strategies or strategic competences, which are the most often, applied by the participants of study, are borrowing including literal translation and language mix. Also, they often applied paraphrase including approximation and circumlocution. According to the findings, it can be concluded that communication strategies are important for learners to notice that breakdown in communication not as some insuperable obstacle to be stayed away but as a great chance for learning. So, it is expected that the teachers help the students to remain in conversation, and so allow them with more input and more opportunities to develop their interlanguage system.